PERTANGGUNGJAWABAN PERUSAHAAN FARMASI DALAM KASUS OBAT YANG MENYEBABKAN GAGAL GINJAL PADA ANAK - Yosephin Priskilla Siregar (2023)
Corporate crime can take several distinct shapes in a variety of industries including the healthcare industry. The manufacturing of medicines containing dangerous ingredients is one type of corporate crime committed in the health sector, particularly pharmaceuticals. This has led to the emergence of the phenomenon of acute kidney failure, which is experienced by hundreds of children spread across several regions in Indonesia. The criminal responsibility of pharmaceutical corporations that produce harmful medicines with Ethylene Glycol and Diethylene Glycol contamination over acceptable levels is the focus of this study, as well as measures to stop the production of drugs that don't meet quality requirements. Using the juridical-normative research methodology, this study's main sources for information include the doctrines of experts and the statutory regulations Law No. 1 of 2023 concerning the Criminal Code, Law No. 8 of 1999 concerning Consumer Protection, and Law No. 36 of 2009 concerning Health. The corporation that creates the pharmaceuticals must be held accountable for these activities as a corporate actor that develops drugs with hazardous components that cause acute kidney failure in survivors, whether it be the management, the firm itself, or both. To stop similar occurrences from happening in the future, preventative measures are also required in addition to punitive actions taken against firms. Law enforcement officials and corporate actors must take a proactive approach as a result. Additionally, for the community to be able to fulfil its part in preventing the occurrence of similar crimes.